PKM Pentingnya Akuntansi bagi Pelaku UMKM - Susilawati, Made; Meilandri, Detti; Nurhanimah; Ningrum, Endah Prawesti; Chandra, Johnny (Cattleya Darmaya Fortuna, 2025)
Community service is carried out to improve the understanding of MSME entrepreneurs regarding the importance of accounting in business management. Many MSME entrepreneurs in Kupang City do not yet have a good financial recording system, making it difficult to monitor the development of their business. Through this activity, participants are given training on the basics of accounting, such as recording transactions, preparing profit and loss reports, and simple balance sheets. The methods used include counseling, direct practice training, and mentoring. The results of the activity showed an increase in participants' understanding of the functions and benefits of accounting in supporting business sustainability. Participants also began to apply simple financial recording in daily operations. Through this PKM, MSME entrepreneurs are expected to be able to manage their business finances more professionally and be able to increase competitiveness in the market.